Halo mergers enhance the growth of massive black hole seeds - Prole, Lewis R.; Regan, John A.; Whalen, Daniel J.; Glover, Simon C. O.; Klessen, Ralf S. (Astronomy and astrophysics, 2024)
Context. High-redshift observations of 109 M⊙ supermassive black holes (SMBHs) at z ∼ 7 and ‘little red dots’ that may host over-massive black holes (BHs) at z > 4 suggests the existence of so-called heavy seeds (> 1000 M⊙) in the early Universe. Recent work has suggested that the rapid assembly of halos may be the key to forming heavy seeds early enough in the Universe to match such observations, as the high rate of accretion into the halo suppresses the cooling ability of H2, allowing it to quickly accrete up to the atomic cooling limit of 107 M⊙ prior to the run-away collapse of baryonic gas within its dark matter (DM) potential, without the need for extreme radiation fields or DM streaming velocities. Aims. While the rapid assembly of halos can lead to increased halo masses upon the onset of collapse, it remains unclear if this leads to higher-mass BH seeds. As a common route for halos to grow rapidly is via halo-halo mergers, we aim to test what effects such a merger occurring during the initial gas collapse has on the formation of BH seeds. Methods. We performed simulations of BH seed formation in four distinct idealised halo collapse scenarios: an isolated 106 M⊙ minihalo, an isolated 107 M⊙ atomic halo, the direct collision of two 107 M⊙ halos, and a fly-by collision of two 107 M⊙ halos. We simulated the collapse of the gas down to scales of ∼0.0075 pc before inserting sink particles as BH seeds and captured a further 10 Myr of accretion. Results. We have shown that halo collisions create a central environment of increased density, inside which BH seeds can accrete at higher rates. For direct collisions, the gas density peaks are disrupted by the interaction, as the collisionless DM peaks pass through each other while the colliding gas is left in the centre, removing the BH from its accretion source. When the central density peaks instead experience a fly-by interaction, the BH remains embedded in the dense gas and maintains higher accretion rates throughout the simulated period compared to the isolated halo cases. The total simulated period was 70 Myr, and we followed the evolution of the BH for the final 10 Myr. The BH spends the final 6 Myr embedded in the dense, shocked region. The final mass of the BH is a factor of 2 greater than in the isolated atomic halo case, and a factor of 3 greater than the minihalo case, reaching 104 M⊙ via its 0.03 pc accretion radius. As the maximum halo mass before collapse is determined by the atomic cooling limit of a few times 107 M⊙, the ability of halo-halo mergers to further boost the rates of accretion onto the central object may play a crucial role in growing SMBH seeds, which is needed to explain recent observations of seemingly over-massive BHs at high redshifts.
Gesehen am 12.01.2026